2021
DOI: 10.4149/neo_2021_210205n180
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-fetoprotein/endoplasmic reticulum stress signaling mitigates injury in hepatoma cells

Abstract: Alpha-fetoprotein (AFP) and endoplasmic reticulum (ER) stress play multiple roles in hepatocellular carcinoma. Here, we analyzed the crosstalk between AFP and ER stress in human hepatoma cells. We induced ER stress in human hepatoma cell lines (HepG2 and SK-Hep1 cells) with thapsigargin (TG, an ER stress inducer), and mitigated ER stress with 4-phenylbutyrate acid (4-PBA, an ER stress inhibitor). AFP expression was knocked down by AFP short hairpin RNA and rescued by the pCI-AFP vector. AFP expression and ER s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
3
2
0
Order By: Relevance
“…The results suggest that the induced AFP expression in the liver by ER stress may enhance the resistance of hepatocytes to apoptosis and necroptosis stimulators, alleviating liver injury. Interestingly, we found that AFP silencing also exacerbated the ER stress, but lowed ATF6 expression in LO2 cells and in hepatocytes of liver tissues in mice, consistent with our previous observation[ 15 ]. These findings suggest that intracellular AFP induced by the ATF6 signaling may feedback-attenuate the ER stress-induced hepatocyte apoptosis and necroptosis, partially by up-regulating ATF6 expression.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The results suggest that the induced AFP expression in the liver by ER stress may enhance the resistance of hepatocytes to apoptosis and necroptosis stimulators, alleviating liver injury. Interestingly, we found that AFP silencing also exacerbated the ER stress, but lowed ATF6 expression in LO2 cells and in hepatocytes of liver tissues in mice, consistent with our previous observation[ 15 ]. These findings suggest that intracellular AFP induced by the ATF6 signaling may feedback-attenuate the ER stress-induced hepatocyte apoptosis and necroptosis, partially by up-regulating ATF6 expression.…”
Section: Discussionsupporting
confidence: 92%
“…Low levels of serum AFP are detected in patients with chronic liver disease, and are positively correlated with the degrees of liver damages[ 8 , 24 ]. Although high levels of AFP expression were detected in mouse livers, we did not detect abnormally high levels of serum AFP in liver-injured mice, consistent with our observation in hepatoma cells[ 15 ]. These indicated that ER stress induced intracellular AFP expression by limiting its secretion.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Then, cells were treated with TG (1.0 μmol/L) for 36 h to induce hepatic ER stress. Previous studies demonstrated that SK-Hep1 cells were more sensitive to ER stress inducers; therefore, an induction dose of 0.25 μmol/L TG was used 62 .…”
Section: Methodsmentioning
confidence: 99%